Vias institucionalizadas de acesso a medicamentos em um município brasileiro - Aragão, Samia Cristina Rodrigues Borges (2015)
Medications readily available for the Brazilian population in the Unified Health System (SUS) is one of the health policies and programmes that meet the constitutional right of every Brazilian citizen. Lots of regulations have been created for medication distribution through Pharmaceutical Assistance (PA), however the user of the medication sometimes is confused and how obtain it. Describe the pathway and regulations for medication distribution through the public health policies in a city. Qualitative research held from December 2014 to January 2015, which focused on normative and explanatory documents for the public health system in Brazil in the city of Goiania in Goias state. An extensive bibliographic research has been carried out on this topic to fundament the analysis of the documents. The medication right is defined in the Brazilian’s constitution, legislation and regulatory acts for the private labour sector and public through co-payment as a means for medication access. In Goiania establishes the Pharmaceutical Assistance (PA) as it is for the Pharmacy and Therapeutics Committee (CFT), SMS Pharmacies, publicizing information related to drugs, health programmes such as “Farmácia Popular“ and the administrative access road through the Division of Assets Evaluation and non-Standardized Services (DABSNP) as a way to meet the demands of those users who have failed treatment through public policies. The medications available through the public policies are organized by REMUNE and the list of medications with high costs of Juarez Barbosa. The public health programmes “Farmácia Popular” and “Saúde Não Tem Preço“ are the ways of co-payment and free of charge. Medications not listed on REMUNE or unavailable to the user are available via administrative process to prevent lawsuit. Conclusion: The medication right is defined in the Brazilian’s constitution, and public policies with little or no influence of local city government. However, how to obtain it, the list of available medication, and the requirements is a local governmental duty. Therefore, the policies defined for such programmes can facilitate the understanding of the network comprising the Pharmaceutical Assistance (PA) in the Brazil’s Unified Health System (SUS).